2010
DOI: 10.1038/ejcn.2010.198
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of zinc from NutriSet zinc tablets compared with aqueous zinc sulfate

Abstract: Background/Objectives: The apparent widespread extent of zinc (Zn) deficiency in developing countries and the efficacy of oral Zn supplements as an adjunct to oral rehydration therapy make oral Zn supplementation an increasingly important modality in clinical medicine and public health. In this study we aimed to compare the relative bioavailability of oral doses of 30 mg of Zn in two dosing forms Subjects/Methods: In total, 10 healthy male volunteers ingested oral Zn doses with 200 ml plain water at about 0830… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Tran et al [59] found that the fractional absorption of zinc ranged from 0.62 to 0.73 for aqueous zinc sulfate doses of 2 mg to 15 mg, with declining fractional absorption for 20 and 30 mg dosing. Solomons et al [60] compare the absorption of aqueous zinc sulfate with the absorption of NutriSet tablets, and find that aqueous zinc administration doubles the bioavailability of zinc compared to the NutriSet tabs. To date, no evidence on the health impact of aqueous zinc is available.…”
Section: Resultsmentioning
confidence: 99%
“…Tran et al [59] found that the fractional absorption of zinc ranged from 0.62 to 0.73 for aqueous zinc sulfate doses of 2 mg to 15 mg, with declining fractional absorption for 20 and 30 mg dosing. Solomons et al [60] compare the absorption of aqueous zinc sulfate with the absorption of NutriSet tablets, and find that aqueous zinc administration doubles the bioavailability of zinc compared to the NutriSet tabs. To date, no evidence on the health impact of aqueous zinc is available.…”
Section: Resultsmentioning
confidence: 99%
“…The upper limit for daily zinc intake in an adult is 40 mg. 22 However, when 30 mg of elemental zinc was given orally to humans, it resulted in an only 1.8-fold increase in plasma zinc in the first 4 hours. 23 A similar study in humans where elemental zinc (30 mg/d) or placebo were given orally for 6 months showed a statistically significant in the plasma zinc from 14.18±1.75 μmol/L in the placebo group to 17.18±3.48 μmol/L in the zinc group. 24 Oral delivery of zinc is affected by several factors, including normal variations in gut zinc absorption, dietary factors such as the presence of phytate, and interactions with other metal ions.…”
Section: Dosing Rationalementioning
confidence: 89%
“…82 When 30 mg of elemental zinc was given orally to humans, it resulted in an only 1.8-fold peak increase in plasma zinc to 27 ± 12 μmol/L from a baseline of 15 ± 5.1 μmol/L over 4 hours. 82 Feillet-Coudray et al showed oral supplementation of 30 mg zinc per day over 6 months resulted in a marginal increase in the plasma zinc from 14 ± 1.7 μmol/L in the placebo group to 17 ± 3.5 μmol/L in the zinc group. 83 Using a preclinical large animal model of sheep, which closely resemble the pathophysiology observed in humans, a study by O'Kane et al showed that plasma zinc levels needed to be raised by 7-fold from a baseline concentration of 11 ± 0.4 μmol/L to 70 ± 5.8 μmol/L to protect the sheep against renal ischaemia reperfusion injury.…”
Section: Variation In Zinc Bioavailabilitymentioning
confidence: 99%
“…Zinc is primarily supplemented orally. Solomons et al demonstrated that different formulations of oral zinc had different bioavailability; for example, consumption of 30 mg of zinc as Nutriset tablet (ZinCfant®) resulted in lower plasma zinc when compared to an aqueous solution of zinc sulphate which contained the same amount of elemental zinc 82 . When 30 mg of elemental zinc was given orally to humans, it resulted in an only 1.8‐fold peak increase in plasma zinc to 27 ± 12 μmol/L from a baseline of 15 ± 5.1 μmol/L over 4 hours 82 .…”
Section: Variation In Zinc Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation